Pelatihan Penyusunan Uraian Tugas pada Pegawai Rumah Sakit Milik Pemerintah Provinsi Sulawesi Selatan - Andi Indahwaty Sidin; Nur Arifah; Nurmala Sari; Ummu Kalsum (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The job description is an important element in performance management. The performance achievements of hospitals owned by the South Sulawesi provincial government in the last 3 years have shown less than optimal results. To improve the performance of the hospital, it is necessary to redesign the current job description. This activity aims to improve comprehensive knowledge and skills regarding the preparation of job descriptions for performance improvement in government hospitals belonging to the province of South Sulawesi. The training participants were 21 employees from 7 hospitals owned by the South Sulawesi Provincial Government. The method used is the provision of education in the form of lectures, discussions, group assignments, and presentations. The results of the evaluation found that the average level of knowledge of participants before the training was only 2.38 and then increased to 5.19 after the training. In addition, after the training, the participants have been able to review and compile their job descriptions in the hospital. It is hoped that this training can become a training of trainers so that those who have completed the training can become presenters to train other employees where they work.